Autosomal Recessive Limb Girdle Muscular Dystrophy In A Complex Consanguineous Family: The First Cases Series In Indonesia - Nydia Rena Benita Sihombing; Nurin Aisyiyah Listyasari; Sultana MH Faradz (Journal of Biomedicine and Translational Research, 2017)
Background: Limb girdle muscular dystrophy (LGMD) is a neuromuscular abnormality with clinical heterogeneity and various severity, where over 30 subtypes have been identified. Meanwhile, molecular diagnosis of LGMD is not commonly carried out in Indonesia. We present a large pedigree of familial LGMD, with over 14 years of follow-up.Case Presentation: A 12-year old female patient came with muscle weakness. She had toe walking since age of 6, followed by calf hypertrophy for over three years. Family history revealed complex consanguinity. Her younger sister and her parents’ cousin had similar condition, with the latter was already bedridden.Physical examination results were waddling gait, lordotic spine, and absent deep tendon reflexes. Muscle biopsy showed sign of dystrophic process. Immunoperoxidase staining of some proteins resulted normal. Single nucleotide polymorphism (SNP) array in two siblings revealed homozygosity on chromosome 15 containing CAPN3 gene of LGMD2A subtype.Recently, the patient is wheelchair bound and undergoes rehabilitation. Her sister is still able to walk with abnormal gait, while her parents’ cousin had passed away in age 55. From the multiple consanguinity, it could be concluded as autosomal recessive type LGMD.Conclusion: A large family with LGMD from Indonesia was presented with more than 14 years of care. Clinical diagnosis was made based on physical and additional examination, however molecular analysis for establishing definitive diagnosis is still limited. Further studies such as targeted or whole exome sequencing is warranted to elucidate the cause of disease. Long-term evaluation and supportive care, in addition to proper counseling may increase quality of life.